2008
DOI: 10.1126/science.1155492
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Radio Jet in an Erupting Dwarf Nova

Abstract: Astrophysical jets seem to occur in nearly all types of accreting objects: from supermassive black holes to young stellar objects. Based on X-ray binaries, a unified scenario describing the disc/jet coupling has evolved and extended to many accreting objects. The only major exceptions are thought to be cataclysmic variables: Dwarf novae, weakly accreting white dwarfs, show similar outburst behaviour as X-ray binaries but no jet has yet been detected. Here we present radio observations of a dwarf nova in outbur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
202
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(226 citation statements)
references
References 25 publications
23
202
1
Order By: Relevance
“…Such comparisons could be problematic because LX does not provide a good estimate for Pacc in supermassive BHs as it does for XRBs (Pellegrini 2005). Nevertheless, Merloni & Heinz (2007) and Körding et al (2008) both found the estimates of the scaled jet power compared to the accretion power for Cygnus X-1 to be consistent with those of their AGN samples, albeit with large uncertainties comparable to the uncertainties in the jet power that we find in this work. In contrast, King et al (2013) claimed to find a discrepancy between the jet and wind-scaling correlations with the bolometric luminosity and the values found for Cygnus X-1 using different scaling relations.…”
Section: The Black Hole Jetsupporting
confidence: 67%
“…Such comparisons could be problematic because LX does not provide a good estimate for Pacc in supermassive BHs as it does for XRBs (Pellegrini 2005). Nevertheless, Merloni & Heinz (2007) and Körding et al (2008) both found the estimates of the scaled jet power compared to the accretion power for Cygnus X-1 to be consistent with those of their AGN samples, albeit with large uncertainties comparable to the uncertainties in the jet power that we find in this work. In contrast, King et al (2013) claimed to find a discrepancy between the jet and wind-scaling correlations with the bolometric luminosity and the values found for Cygnus X-1 using different scaling relations.…”
Section: The Black Hole Jetsupporting
confidence: 67%
“…For all but the last, their velocities are (at least mildy) relativistic (Reipurth & Bally 2001;Körding et al 2008a;Mirabel & Rodríguez 1999). Despite a wealth of observations, the launch mechanism of jets has so far remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Kording et al 2006;Kording et al 2008;Tudose et al 2009), argues for an ejection process that is also independent of the central object. This seems to be confirmed by the lack of correlation between jet power or jet velocities and measured values of black hole spins (Fender et al 2010).…”
Section: Introductionmentioning
confidence: 99%